1997
DOI: 10.1103/physrevb.56.10459
|View full text |Cite
|
Sign up to set email alerts
|

Competing growth mechanisms of Ge/Si(001) coherent clusters

Abstract: The growth of Ge three-dimensional coherent clusters on Si͑001͒ during gas source molecular-beam epitaxy and post-deposition anneals has been investigated using in situ elevated-temperature scanning tunneling microscopy. By monitoring the growth of individual so-called ''hut'' clusters, this technique allowed us to separate various factors that may affect the final size distribution of entire cluster ensembles. It has been found that during the course of epitaxy the hut clusters grow by nucleation and growth o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 40 publications
3
45
0
Order By: Relevance
“…Here we examine the growth of Ge islands with ͕105͖ facets, the so-called "hut" clusters [7][8][9][10]. Since such Ge islands are the smallest observed on Si(001) [1,11], they are best suited as nanometer sized islands.…”
Section: Kinetically Self-limiting Growth Of Ge Islands On Si(001)mentioning
confidence: 99%
“…Here we examine the growth of Ge islands with ͕105͖ facets, the so-called "hut" clusters [7][8][9][10]. Since such Ge islands are the smallest observed on Si(001) [1,11], they are best suited as nanometer sized islands.…”
Section: Kinetically Self-limiting Growth Of Ge Islands On Si(001)mentioning
confidence: 99%
“…To add complexity and interest to this story, under certain growth conditions a bimodal or trimodal distribution of island sizes has been observed: examples exist for the Ge/Si (Goldfarb et al, 1997a;Goryll et al, 1997;Kamins et al, 1997;Medeiros-Ribeiro et al, 1998) and InP/GaInP systems (Johansson et al, 1998;Lee et al, 1997;Ponchet et al, 1995;Reaves et al, 1996). In a beautiful STM study of the Ge/Si system (MedeirosRibeiro et al, 1998), it was shown that the two peaks in the island size distribution correspond to two different island shapes.…”
Section: Introductionmentioning
confidence: 96%
“…1(d) using characteristic values for the Ge=Si001 system [22]. While the calculations indicate isotropic growth for s t e 0 100 nm ( 0 37 nm), real huts seem to begin elongation already at a stable nucleus size of about 5-8 nm [23], if at all [e.g., the island in Fig. 1(a) does not show any anisotropic elongation].…”
mentioning
confidence: 98%